Filling the Blank Page: A Comparison of Carson McCullers’ The Heart is a Lonely Hunter and Jerzy Kosinski’s Being There - González Groba, Constante (Revista de Estudios Norteamericanos, 2019)
ABSTRACT: RESUMEN: